Pelaksanaan Kewenangan Pengadilan Tinggi Tata Usaha Negara Medan dalam Menyelesaikan Sengketa Pemberhentian Pegawai Negeri Sipil di Provinsi Riau - Silm Oktapani; Robert Libra; Zulkarnaen Noerdin (AHKAM, 2026)
In the governance of modern states, the state civil apparatus (Aparatur Sipil Negara, ASN), including civil servants (Pegawai Negeri Sipil, PNS), occupies a strategic position as the frontline in implementing public policies and delivering public services, making legal certainty and protection of PNS rights crucial for administrative justice and bureaucratic stability. This study aimed to examine the exercise of jurisdiction by the Medan High Administrative Court (Pengadilan Tinggi Tata Usaha Negara, PTTUN Medan) in resolving PNS dismissal disputes in Riau Province under Supreme Court Regulation No. 2 of 2023 (Peraturan Mahkamah Agung Nomor 2 Tahun 2023), and to analyze its implications for PNS access to justice. This is a sociological legal study with an empirical approach that investigates how the regulation of jurisdiction is operationalized in practice, taking into account geographical, administrative, and institutional contexts. The findings show that the geographical distance between Riau Province and Medan City functions as a determining variable affecting PNS access to justice, as it increases the time, cost, and procedural complexity associated with filing claims before PTTUN Medan. At the same time, Supreme Court Regulation No. 2 of 2023 comprehensively reaffirms the status of PTTUN as the competent court of first instance to examine, decide, and resolve PNS dismissal disputes and employment termination of government employees with work agreements (PPPK) after the completion of administrative remedies before the Badan Pertimbangan ASN (BPASN). In conclusion, the strengthening of PTTUN Medan’s jurisdiction through this regulation provides legal certainty for the resolution of PNS dismissal disputes, while simultaneously highlighting access-to-justice challenges for PNS in Riau that must be addressed through policy design and administrative court governance that place greater emphasis on ease of access for justice seekers in the regions.